Does Unplanned Soft Tissue Sarcoma Surgery Have a Negative Effect on Prognosis? - EROL, BÜLENT (TAYLOR & FRANCIS INC, 2022)
Background We aimed to compare the oncological outcomes of patients who underwent re-excision following unplanned surgery and those who underwent planned surgery. Methods Patients who were referred to our hospital after a mass was inappropriately resected and reported to have a malignant pathology with a positive surgical margin, as well as patients diagnosed with malignant soft tissue tumors, and operated on following a multidisciplinary assessment and staging between 2012 and 2018. All patients were followed up at least 6 months. Results Our study included a total of 125 patients. Forty percent (n = 50) underwent unplanned excision and sixty percent (n = 75) underwent planned excision.There was no statistically significant difference in the survival curves between the two groups (p = 0.248). Tumor size was larger, and the rate of deep-localized tumors was higher in patients undergoing planned surgery than in the unplanned surgery group (p = 0.001). The rate of tumors localized in the upper extremities was significantly higher in the unplanned surgery group than in the planned surgery (p = 0.033). MRI examinations could detect residual tumors with an accuracy of 80%. Age (>48 years), tumor size (>8 cm), tumor grade (grade 3), and distant organ metastasis at follow-up, which were among risk factors found to have a significant effect on mortality. Conclusion Patients undergoing re-excision after an inappropriate resection and undergoing planned resection had a similar prognosis. Superficial, upper extremity-localized, and relatively small-size tumors are more prone to inadequate surgical resection. MRI can be used to detect residual tumors at a high rate in patients who have undergone unplanned surgery. Distant organ metastasis is the most important factor affecting survival.
Keywords: Soft tissue sarcoma; unplanned excision; oncologic outcomes; residual disease; local recurrence; re-excision surgery; RE-EXCISION; RESIDUAL DISEASE; IMPACT; RERESECTION; OUTCOMES